Implementation of Wordwall Based Learning Modules to Improve Student Learning Activities in Elementary Schools - Sari, Siti Mayang; Katrunnada, Katrunnada; Akmaluddin, Akmaluddin (FKIP - Universitas Riau, 2025)
Education is a conscious and planned effort to develop human resources towards better and better quality. The fourth grade teacher, Mrs. YS, said that during the teaching and learning process teachers still often carry out learning using the lecture method as is generally used so that the learning process occurs conventionally and there is a lack of student activity during learning so that student learning outcomes are still relatively low. This research aims to examine the implementation of Wordwall-based learning in elementary schools and identify its impact on students' motivation and understanding in learning.This research uses quantitative research with a quasi-experiment approach. The data analysis technique used in this research includes descriptive analysis. The research results found that the implementation of Wordwall-based learning in elementary schools had a positive impact on improving student learning outcomes and interest. Classes that use Wordwall as a learning medium show a more significant increase in learning outcomes compared to classes that use conventional methods. This is shown by the difference in the increase in posttest scores between the experimental group and the control group, where the experimental group experienced an increase of 29%, while the control group only increased 11.2%.